Gawad Plaridel lecture 2013 - Lacaba, Jose F. (2014)
Access online through this link: https://www.plarideljournal.org/article/gawad-plaridel-lecture-2013
Keywords: UP Gawad Plaridel; Pascual, Alfredo E